Supporting the emergence of knowledge communities in industrial association groups in the construction sector - Lucas Soares, António (2021)
association group in the construction sector. This system is a result of the Know-Construct project which aimed at providing association sponsored SME communities of the construction sector with a sophisticated information management platform and community building tools for knowledge sharing and customer support. The paper begins by characterizing the so-called construction industry knowledge community (CIK). The generic architecture of the supporting system (Knowledge Community Support - KCS and Customer Needs Management - CNM) is described, in terms of information and knowledge management, community building facilities and semantic resources management. The Know-Construct project decided to re-use, as far as possible, existing ontologies, classification systems and other semantic resources to develop a system for the integration, management and reuse of the area specific knowledge. Part of the paper describes the approach followed, as well the lessons learned. The final part of the paper depicts the approach to the actual introduction of the system in the community.